2018
DOI: 10.1016/j.ejmech.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small-molecule inhibitors of USP2a

Abstract: USP2a is a deubiquitinating protease that rescues its target proteins from destruction by the proteasome by reversing the process of protein ubiquitination. USP2a shows oncogenic properties in vivo and has been found to be a specific activator of cyclin D1. Many types of cancers are addicted to cyclin D1 expression. Targeting USP2a is a promising strategy for cancer therapy but little progress has been made in the field of inhibition of USP2a. Using NMR-based fragment screening and biophysical binding assays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…A nuclear magnetic resonance (NMR)-based fragment screening led to the discovery of compound STD1T as a selective USP2 inhibitor (IC 50 = 3.3 μM) ( Figure 6 ) [ 120 ].…”
Section: Recent Development Of Usp Inhibitorsmentioning
confidence: 99%
“…A nuclear magnetic resonance (NMR)-based fragment screening led to the discovery of compound STD1T as a selective USP2 inhibitor (IC 50 = 3.3 μM) ( Figure 6 ) [ 120 ].…”
Section: Recent Development Of Usp Inhibitorsmentioning
confidence: 99%
“…Hence, these adipokines appear to modify USP2 expression in a manner that leads to changes in cyclin D1 levels and subsequent cell cycle progression. Since the intracellular content of cyclin D1 is a determinant for tumorigenesis in certain types of tumors, cyclin D1 has been used as an index in the exploration of USP2 inhibitors as anti-tumor drugs [40,42,43]. Similar to cyclin D1, USP2-1 likewise stabilizes cyclin A1, which also participates in the proliferation of bladder cancer cells [24].…”
Section: Tumorigenesismentioning
confidence: 99%
“…ML364 was reported as a small molecule inhibitor for USP2 and has been proven to evoke cell cycle arrest, cyclin D1 degradation, and inhibition of homologous recombination-mediated DNA repair [42]. Additionally, several studies have reported other chemical inhibitors for USP2, such as isoquinoline-1,3-dione-based compounds [172], chalcone-based compounds [173], 5-(2-thienyl)-3-isoxazoles [43], and a lithocholic acid derivative [40]. Furthermore, other reports have demonstrated that previously established anti-cancer drugs inhibit USP2 activity.…”
Section: Perspectivesmentioning
confidence: 99%
“…ML364 selectively inhibits USP2 and thereby increases mitochondrial ROS levels, modulating the morphology and membrane potential of the mitochondria [240]. Two other small molecule inhibitors of USP2a, derivatives of 5-(2-thienyl)-3-isoxazoles, have been identified using NMR-based fragment screening and biophysical binding assays [210].…”
Section: Other Small Molecule Dub Inhibitorsmentioning
confidence: 99%